Reactive stability of promising scalable doped ceria materials for thermochemical two-step CO2 dissociation. Issue 14 (15th March 2018) - Jacot, R.; Naik, J. Madhusudhan; Moré, R.; Michalsky, R.; Steinfeld, A.; Patzke, G. R.
Abstract : This work reports an improved and stable oxygen exchange capacity (OEC) of optimized doped ceria Ce1− x M x O2− δ (M = Zr, Hf, Nb) materials for two-step thermochemical CO2 splitting over 50 consecutive redox cycles (7 days). Abstract : Metal-doped ceria (Ce1− x M x O2− δ ) is an attractive redox-active material for thermo/electrochemical synthesis of renewable fuels due to its high mixed ionic/electronic conductivity and variable valence (Ce 4+ /Ce 3+ ) and oxygen nonstoichiometry ( δ ) at high temperatures. Previously, we have investigated all 26 potentially tetravalent dopants for efficient thermochemical splitting of CO2 . Here, we fine-tune the dopant activity ( x = 0.10 Zr 4+, 0.10 Hf 4+, 0.07 Ta 5+, and 0.05 Nb 5+ ) of all thermally stable ceria materials with an oxygen exchange capacity (OEC) surpassing that of pristine ceria (CeO2− δ ), and we employ thermogravimetric analysis to evaluate long-term stability of their OEC over 50 consecutive redox cycles. Each cycle swings between 40 min ceria oxidation with approximately 500 mbar CO2 at 1000 °C and 90 min ceria reduction in about 0.01 mbar O2 at 1500 °C. Along with analyses of phase purity and stability (PXRD), of composition and dopant concentration (EDX and ICP-MS), and of sintering via SEM, the cycling results show long-term stable OEC and kinetics of the oxygen exchange for Zr-, Hf-, and Nb-doped ceria, despite their distinctly sintered particle surfaces. This attractive performance is rationalized by characterizing oxidation states and oxygen vacancies and by excluding surface carbonation through Raman and FT-IR spectroscopy. Furthermore, we find that introducing stable oxygen vacancies in Ce0.95 Hf0.05 O2− δ by doping with additional 5% lower-valent Li +, Mg 2+, Ca 2+, Y 3+, and Er 3+ does not significantly accelerate the oxygen exchange kinetics. From this first comprehensive long-term stability study of systematically optimized ceria, we propose ceria co-doped with permutations of Hf 4+, Zr 4+, and Nb 5+, yielding an optimal average dopant radius of 0.8 Å, as the benchmark redox material for thermochemical production of solar fuels.